THE ROLE OF BLENDED LEARNING IN ENHANCING STUDENTS’ WRITING PARAGRAPH - Dodi Mulyadi; Testiana Deni Wijayatiningsih (JALL (Journal of Applied Linguistics and Literacy), 2020)
The use of efficient and appropriate learning media-based learning is needed at all levels of education.  In English language teaching (ELT) at the university level, the use of media can help to improve paragraph writing. The objective of this study was to determine the effect of Blended Learning on improving learning outcomes of EFL university students' writing paragraphs in English. This quasi-experimental research entailed non-parametric statistical analysis. The results indicated a statistically significant improvement after getting treatment of blended learning.  The average pretest score was 65.9 and the average posttest score was (86.6) which means higher than the pre-test. These results also indicated that the Blended Learning model stimulated students to explore more ideas in writing activities. In addition, the results of the questionnaire showed that 85% of students were enthusiastic and enjoyed the learning process. Since the dearth of the research sample, further research has to be conducted in a broad research sample to be a more generalizable pedagogical implication.Keywords: blended learning, writing, paragraph.